Time diversity analysis for rain fade mitigation in satellite links based on rain rate data - Alam, Md. Moktarul (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Earth–to-satellite links are highly affected by propagation impairments by rain especially those operating at frequencies higher than 10 GHz. The satellite communication system performance suffers from severe degradation at high frequencies in tropical and equatorial climate. Time diversity is one of the workable technique with suitable time delay between successive transmissions which is proposed by many researchers to mitigate rain fade. However, time diversity analysis requires measured rain attenuation data. For future high frequency link design those data are not available at most of the places. Time diversity gain prediction model was proposed by the measured rain attenuation for time diversity improvement which is analyzed by the rest of researchers. Rain rate data were measured using real-time rain gauge for one-year period at IIUM for 2014. A new concept of rain rate with and without time delay is introduced with appropriate equations. Based on the rain attenuation equation with time delay, the complementary cumulative distribution function of rain rate with time delay is presented. One month measured rain rate and rain attenuation is used to verify this concept. The rain attenuation prediction model proposed by ITU-R is used to estimate rain attenuation gain analytically. The analytically obtained gain is compared with measured gain and found close agreement. Hence, this concept has shown that attenuation gain can be easily estimated by using rain rate. A time diversity gain (GA) model is derived based on 1 year measured rain rate in Malaysia. In proposed model, it is used three variables namely rain rate, time delay and frequency. Firstly, rain rate and time delay functions are used together, and constants are derived by regression from rain rate and rain rate gain. Secondly, constant for frequency function is derived from Cumulative distribution function of attenuation predicted by ITU-R and gain obtained analytically. These two functions are combined together and the proposed model of attenuation gain (G_A) is developed. The proposed model is validated using one-year rain rate and rain attenuation data measured at two locations in Malaysia and one location in Japan. The gain predicted by proposed model is almost same with measured gain for Malaysia and the maximum discrepancy is found 8%. It overestimates the measurement in Japan and the maximum error is 34%. However, the rain rate is 40 mm/hr measured in Japan, while it is 125 mm/hr in Malaysia at 0.01%. Analysis shows that the performance of proposed model is more accurate better than model proposed by Matricciani. Hence the proposed model is recommended to use in future for earth to satellite link design by using measured rain rate at any higher frequencies.